Comparative evaluation of antibacterial effects of aqueous extract of Garlic (Allium sativum) and Enrofloxacin following experimental infection with Salmonella typhimurium (PTCC: 1709) in broiler chickens - Benyamine Rahmani-Dizgah; Younes Anzabi; Jafar Rahmani-Kahnamoe (Āsīb/shināsī-i Darmāngāhī-i Dāmpizishkī)
Infection with salmonella bacteria can lead to serious complications for the health of animals as well as humans, and providing effective control strategies is of particular importance. In recent years, the garlic plant (Allium sativum) has received widespread attention in the control of bacterial infections, including salmonella, due to its natural antibacterial properties. Therefore, the present study was conducted to compare the effects of aqueous extract of garlic and enrofloxacin antibiotic against experimental infection caused by Salmonella typhimurium (PTCC: 1709) in broilers. For this purpose, 35 broilers (in 5 groups) were used and antibiogram tests, determination of minimum inhibitory concentration (MIC) and bactericidal concentration (MBC) and total bacterial counts were performed. It was found that experimental infection with the tested bacteria was obtained by using 0.8 ml of microbial suspension according to McFarland standard 1 and after 48 hours. Also, enrofloxacin was able to control the growth of the mentioned bacteria more effectively, so that in the penetration test in the well, the diameter of the non-growth zone was 49 mm and the MIC and MBC were equal to 0.00244% while the mentioned factors for the aqueous extract of garlic were 9 mm, 12.5 and 25%, respectively. On the other hand, there were relatively significant mortalities in the chickens of the positive control group and the group treated with enrofloxacin, while no mortalities were observed in the negative control group and the groups treated with garlic extract (in 2 different doses). It seems that the findings of the present study can be used as a source of scientific information to implement the use of garlic in the poultry industry to control Salmonella infection.